2013
DOI: 10.1371/journal.pone.0074661
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of 5-HT2A Receptor-PDZ Protein Interactions Alleviates Mechanical Hypersensitivity in Carrageenan-Induced Inflammation in Rats

Abstract: Despite common pathophysiological mechanisms, inflammatory and neuropathic pain do not respond equally to the analgesic effect of antidepressants, except for selective serotonin reuptake inhibitors (SSRIs), which show a limited efficacy in both conditions. We previously demonstrated that an interfering peptide (TAT-2ASCV) disrupting the interaction between 5-HT2A receptors and its associated PDZ proteins (e.g. PSD-95) reveals a 5-HT2A receptor-mediated anti-hyperalgesic effect and enhances the efficacy of fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…5-HT 1A , 5-HT 2A and α 1 -adrenoceptors) which then produces anti-nociception, presumably through their downstream mechanisms (Figure 9). The involvement of the three receptors implicated in antinociception in this study has previously been demonstrated (Tasker et al, 1992;Bardin, 2011;Valhondo et al, 2013;Wattiez et al, 2013;Sun et al, 2014). Interestingly,…”
Section: Figuresupporting
confidence: 71%
“…5-HT 1A , 5-HT 2A and α 1 -adrenoceptors) which then produces anti-nociception, presumably through their downstream mechanisms (Figure 9). The involvement of the three receptors implicated in antinociception in this study has previously been demonstrated (Tasker et al, 1992;Bardin, 2011;Valhondo et al, 2013;Wattiez et al, 2013;Sun et al, 2014). Interestingly,…”
Section: Figuresupporting
confidence: 71%
“…Also, TAT-2ASCV enhanced SSRI-induced anti-hyperalgesia [99]. Recent studies identified this process in traumatic neuropathic pain and inflammatory pain models [100,101], as well as the evidence that spinal GABA release and GABA A receptor activation are involved in this process [101,102]. Presently, a final conclusion of the facilitatory or inhibitory role of 5-HT 2A/2C receptors in painrelated circuits in the descending pain system is still not clear.…”
Section: The Role Of Serotonergic System In Descending Pain Modulationmentioning
confidence: 99%
“…In particular, pharmacological studies and knockout mice have demonstrated that 5-HT 2A R and 5-HT 2C R contribute to anxiety and are pharmacological targets for the treatment of anxiety (Weisstaub et al, 2006). Although many studies have investigated the pharmacological regulation of 5-HT 2A R and 5-HT 2C R in psychiatric disorders, a limited number of studies have focused on the contribution of C-terminal 5-HT 2A R and 5-HT 2C R PSD-95/disc large/zona occludens (PDZ)-binding motif interactions with PDZ domain-containing proteins to 5-HT 2 R-related disorders (Abbas et al, 2009;Jones et al, 2009;Magalhaes et al, 2010;Pichon et al, 2010;Wattiez et al, 2013). For example, PSD-95 regulates the actions of atypical antipsychotics on 5-HT 2 Rs and kalirin-7 mediates 5-HT 2 R-dependent modulation of spine morphology (Abbas et al, 2009;Jones et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, PSD-95 regulates the actions of atypical antipsychotics on 5-HT 2 Rs and kalirin-7 mediates 5-HT 2 R-dependent modulation of spine morphology (Abbas et al, 2009;Jones et al, 2009). In addition, disruption of 5-HT 2A R PDZ protein interactions enhances selective serotonin reuptake inhibitor (SSRI) efficacy in neuropathic pain and alleviates mechanical sensitivity to inflammation (Pichon et al, 2010;Wattiez et al, 2013). Thus, the emerging understanding of the importance of PDZ domaincontaining proteins in the regulation of 5-HT 2A R activity will be essential for understanding how the intracellular trafficking of 5-HT 2A R may contribute to the regulation of agonist-stimulated 5-HT 2A R cellular responses (Backstrom et al, 2000;Xia et al, 2003a;Xia et al, 2003b;Gavarini et al, 2006;Jones et al, 2009;Magalhaes et al, 2010;Pichon et al, 2010;Wattiez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%